2011
DOI: 10.7150/ijms.8.537
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of Bacteremia in a Pediatric Patient with Down Syndrome: Sphingomonas Paucimobilis

Abstract: Sphingomonas paucimobilis, is a yellow-pigmented, aerobic, non fermentative, gram negative motile bacillus. S. paucimobilis which is widely found in nature and hospital environments rarely cause serious or life threatening infections. In this report, a case of hospital acquired bloodstream infection due to S. paucimobilis in a patient with Down syndrome who was on treatment for presumed pneumonia is presented.A one year-old child patient who was a known case of Down syndrome and had previously experienced card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 9 publications
1
26
0
7
Order By: Relevance
“…Exposure to high levels of endotoxins has been reported to influence immune responses towards Th2-type immune response [1832]. In addition, Gram-negative bacteria are commonly associated with hospital acquired infections in humans [11262842], indicating greater risk to immune compromised subjects. It is also important to note that the majority of microorganisms identified from most farms are linked to nosocomial infections in humans that usually involve antibiotic-resistant microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to high levels of endotoxins has been reported to influence immune responses towards Th2-type immune response [1832]. In addition, Gram-negative bacteria are commonly associated with hospital acquired infections in humans [11262842], indicating greater risk to immune compromised subjects. It is also important to note that the majority of microorganisms identified from most farms are linked to nosocomial infections in humans that usually involve antibiotic-resistant microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our study detected that this bacterium was resistant to piperacillin, piperacillin/tazobactam, cefotaxime, imipenem, ciprofloxacin, moxifloxacin, and aztreonam, although it has been reported that the susceptibility to third‐generation cephalosporins and fluoroquinolones is variable (Al‐Halawani et al, ; Hsueh et al, ). Other studies reported that S. paucimobilis was resistant to amikacin, ceftazidime, and fluoroquinolones (Toh et al, ), resistant to cefoxitin and ceftazidime (Özdemir et al, ), and to cefotaxime and amikacin (Cheong et al, ). As there are no definitive guidelines for antimicrobial therapy for this bacterial infections, treatment is done with individualized antibiotic therapy according to the in vitro susceptibility profile of clinical isolates (Özdemir et al, ; Pratama et al, ; Toh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…and to cefotaxime and amikacin (Cheong et al, 2008). As there are no definitive guidelines for antimicrobial therapy for this bacterial infections, treatment is done with individualized antibiotic therapy according to the in vitro susceptibility profile of clinical isolates (Özdemir et al, 2011;Pratama et al, 2016;Toh et al, 2011). Some studies recommended fluoroquinolones, third-generation cephalosporins, and carbapenems as excellent drugs of choice as initial therapy for S. paucimobilis infection (Hsueh et al,.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…It was believed that S. paucimobilis was the only specimen of clinical importance; however, recently Sphingomonas mucosissima and Sphingomonas adhesiva also have been related to human infection 2 , 3. These bacilli are ubiquitous in nature (especially in water and soil) and in nosocomial environments causing mild-to-severe community and nosocomial illnesses 1 , 4…”
Section: Discussionmentioning
confidence: 99%